The Prophet - Khalil Gibran (Lahore Ilqa Publication, 2013)
Kahlil Gibran was a Lebanese-American writer and poet, and even though he was considered a literary and political rebel, his works are still celebrated throughout the world. Gibran$1 (Bs most famous work is The Prophet.s
Keywords: The Prophet